Design of a VR-Based Virtual Laboratory for Network Practicum: The Effect of Immersion on Learning Outcomes - Nurpadhillah Junaid; Ramdan Muaqib; Ramdani; Ratu Balgis Nur Latif; Rezki Aulia (Jurusan Teknik Informatika dan Komputer, 2024)
Purpose – This study aims to design and develop a Virtual Reality (VR)-based virtual laboratory for networking practicum and examine the effect of immersion on students’ learning outcomes. Traditional networking laboratories face limitations in infrastructure, accessibility, and scalability, while conventional desktop-based simulations lack immersive interaction. This study argues that immersive VR environments significantly enhance learning performance in networking practicum. Design/methods/approach – A quasi-experimental non-equivalent control group pretest–posttest design was employed involving 62 undergraduate students (32 experimental, 30 control). The experimental group used a VR-based networking lab developed using Unity and Meta Quest 2, while the control group used a conventional 2D simulator. Learning outcomes were measured using a validated 25-item test. Immersion was assessed using the Igroup Presence Questionnaire (IPQ). Data were analyzed using paired and independent samples t-tests, Pearson correlation, and regression analysis (α = 0.05). Findings – The experimental group achieved a significantly higher posttest mean score (M = 82.63, SD = 6.84) compared to the control group (M = 72.14, SD = 7.26), t(60) = 6.02, p < 0.001, with a large effect size (d = 1.48). Immersion showed a strong positive correlation with learning outcomes (r = 0.67, p < 0.001) and explained 45% of variance in posttest scores (R² = 0.45). Research implications/limitations – The study was limited to one institution, a moderate sample size, and short intervention duration, which may affect generalizability. Originality/value – This study provides empirical evidence of the pedagogical effectiveness of immersive VR in networking practicum and demonstrates the significant role of immersion in improving learning outcomes